Effect of Er: YAG laser, phthalocyanine activated photodynamic therapy, and bioactive glass nanoparticles on smear layer removal and push out bond strength of quartz fiber posts to canal dentin: a SEM assessment - Mahmoud, Okba; Zain, Erum (Frontiers in Dental Medicine, 2025)
IntroductionTeeth that have undergone endodontic treatment often suffer a considerable loss in structural strength, necessitating the insertion of a post into the root canal to maintain stability for both restoration and functionality. While NaOCl and EDTA are standard disinfectants, they come with drawbacks such as toxicity to surrounding tissues, potential allergic reactions, interference with resin sealer polymerization, and dentin erosion. Consequently, finding more effective alternatives is crucial.ObjectivesEffectiveness of various contemporary post space disinfectants, i.e., Er: YAG laser, Phthalocyanine (Pc) activated Photodynamic Therapy (PDT), Bioactive glass nanoparticles (BAGNPs) on the removal of the smear layer (SL) and the push-out bond strength (PBS) of quartz fiber post (QFP) to radicular dentin.MethodsForty-eight mature, single-rooted human mandibular premolars were selected for the study. After ensuring proper disinfection, standard root canal procedures were carried out on each tooth. Post space was prepared. The samples were randomly split into four groups based on the post-space disinfection protocols (n = 12). NaOCl + 17% EDTA, Er: YAG laser + 17% EDTA, Pc(PDT) 17% EDTA, and BAGNPs 17% EDTA. SL removing efficiency was evaluated using SEM on two samples from each group. Bonding of QFP was performed in the post space, followed by sectioning of the canal dentin (coronal, middle, apical). The PBS via universal testing machine and failure mode via stereomicroscopy were quantitatively evaluated. ANOVA was used to compare the results across the different groups, accompanied by the Tukey post hoc test p < 0.05.ResultsPost space treated with Er: YAG+ EDTA presented the highest SL removal and maximum PBS. Whereas Group 4 (BAGNPs+EDTA) samples revealed the lowest SL removal efficacy and minimum PBS.ConclusionEr: YAG + EDTA used as a post-space disinfectant showed significantly better results in terms of SL removal and PBS across all three sections compared to the other groups. Er: YAG + EDTA could potentially serve as an alternative to 2.5% NaOCl + EDTA.